Kajian Kemampuan Argumentasi Siswa pada Materi Pokok Animalia Melalui Pendekatan Saintifik di SMA dengan Peringkat Akreditasi yang Berbeda - Tantri Dewantari; Neni Hasnunidah; Dina Maulina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the differences in the argumentation ability of students in high school with different accreditation ratings. The method used is a survey with an ex post facto research design and a sample selection technique using purposive sampling. The results of the student's argumentative ability test were analyzed statistically with the ANOVA test with a significance level of 5% and the data from interviews and teacher questionnaires were analyzed descriptively. The results showed that the argumentation ability of students in schools with accreditation ratings A was significantly different from those with accreditation ratings B and C. In addition, the argumentation ability of students in schools with accreditation rating B was significantly different from those with accreditation rating C. In conclusion, the average value of argumentation ability of students in high school with accreditation ratings of A, B and C on the subject matter of Animalia has a significant difference. Keywords: Accreditation, Animalia, Argumentation, Scientific Approach